Re-evaluation of prophylactic cranial irradiation in limited-stage small cell lung cancer: a propensity score matched analysis. (6th July 2021) - Inoue, Yuko; Tsujino, Kayoko; Sulaiman, Nor Shazrina; Marudai, Mitsuru; Kajihara, Akifumi; Miyazaki, Shuichiro; Sekii, Shuhei; Uezono, Haruka; Ota, Yousuke; Soejima, Toshinori
Abstract: We attempted to re-evaluate the efficacy of prophylactic cranial irradiation (PCI) in limited-stage small cell lung cancer (LS-SCLC) with more recent data. A total of 179 patients with LS-SCLC received radical thoracic radiotherapy and chemotherapy at our institution between 1998 and 2018. One hundred twenty-eight patients who achieved complete response (CR), good partial response (PR), and PR without progression for at least for one year after initial therapy were enrolled in this study. These patients were divided into a PCI group (group A, n = 43), and a non-PCI group (group B, n = 85). Survival outcomes were retrospectively evaluated. Because several background factors differed significantly between groups A and B, propensity score (PS) matching was performed as 1:1 match of the two groups. Finally, we analyzed 64 patients (group A/B = 32/32). Median follow-up periods were 53 and 31 months in groups A and B, respectively. There were no significant differences between the groups' backgrounds. Two-year overall survival (OS) rates were 77% in group A and 62% in group B (p = 0.224). Two-year brain metastasis free survival (BMFS) rates were 85% in group A and 57% in group B (p = 0.008). The number of patients who underwent a brain imaging test for confirmation of no brain metastasis (BM) after radical thoracic radiotherapy and chemotherapy (before PCI) was 84 (group A/B = 32/52). A PS matched analysis for cases of pre-PCI brain imaging group, two-year OS rates for group A/B were 73/59% (p = 0.446). Two-year BMFS rates for group A/B were 91/52% (p = 0.021). Retrospectively, PS matched analysis revealed that adding PCI to LS-SCLC patients who achieved good thoracic control significantly improved BMFS, but OS did not improve.